Je sais pourquoi chante l'oiseau en cage - Angelou, Maya; Besse, Christiane (Le Livre de poche, 2012)
« Dans ce récit, considéré aujourd'hui comme un classique de la littérature américaine, Maya Angelou relate son parcours hors du commun, ses débuts d'écrivain et de militante dans l'Amérique des années 1960 marquée par le racisme anti-Noir, ses combats, ses amours. Son témoignage dénué de la moindre complaisance, révèle une personnalité exemplaire. À la lire, on mesure mieux encore le chemin parcouru par la société américaine en moins d'un demi-siècle. »-- Quatrième de couverture.
Keywords: 1900-1999; afro-féminisme; amériques; antiracisme; approches et analyses; arts; biographie; cours; discipline; féminisme afroaméricain; lit2815; premier cycle; périodes historiques; racisme; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; états-unis; études littéraires

Life notations of Daisy Sweeney: Reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.
Keywords: 1900-1999; afro-féminisme; amériques; approches et analyses; discipline; femmes* noires; histoire et politique; maternité; montréal; musique; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

The master’s tools will never dismantle the master’s house - Lorde, Audre (Sister outsider: essays and speeches, 2007)
Keywords: afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; fem3600; féminisme afroaméricain; histoire et politique; lesbianisme; militance; premier cycle; régions géographiques; thématiques; émotions; états-unis; études littéraires

The art of history African American women artists engage the past - Collins, Lisa Gail (Rutgers University., 2002)
In this lively and engaging book, Lisa Gail Collins examines the work of contemporary African American women artists. Her study comes at a time when an unprecedented number of these artists-photographers, filmmakers, painters, installation and mixed-media artists-have garnered the attention and imagination of the art-viewing public. To better understand the significance of this particular historical moment in American visual arts, Collins focuses on four "problems" that recur when these artists confront their histories: the documentation of truth; the status of the black female body; the relationship between art and cultural contact and change; and the relationship between art and black girlhood. By examining the social and cultural histories which African American women artists engage, Collins illuminates a dialogue between past and present imagemakers. The Art of History is a major contribution to the study of American visual culture. It will be of use to both scholars and students in art history, African American studies, American studies, and women's studies.
Keywords: afro-féminisme; amériques; approches et analyses; arts visuels et médiatiques; corps; cours; discipline; fem1000; femmes* afro-américaines; féminisme afroaméricain; féminismes noirs; pratiques féministes; premier cycle; régions géographiques; thématiques; états-unis

Sula - Morrison, Toni; Alien, Pierre (10-18. Série Domaine étranger, 1994)
Dans l'Ohio des années 20, deux petites filles noires s'inventent ensemble une vie meilleure. Mais l'âge venant, tandis que Nel se plie à son rôle de mère et d'épouse, Sula choisit de conquérir ailleurs sa liberté. Pour tous, elle devient la scandaleuse, la dévoyée. Et doit se défendre, quarante ans plus tard, contre une société soumise à la vérité des autres...
Keywords: 1900-1999; afro-féminisme; amériques; approches et analyses; arts; cours; discipline; féminisme afroaméricain; lit2815; premier cycle; périodes historiques; roman; régions géographiques; thématiques; écriture des femmes*; états-unis; études littéraires